Sustainable implementation of a frailty education program for formal health care providers - Sargent, Matthew J.; Lin, Margaret Chen-Mei; Park, Grace; Parsons, Shannon; Freeman, Shannon (Frontiers in Public Health, 2025)
BackgroundFrailty is a significant contributor to morbidity and mortality and places considerable strain on healthcare systems. Frailty education is essential for shaping professional attitudes and enabling proactive care. The Canadian Frailty Network’s AVOID (activity, vaccination, optimization of medications, interactivity, diet) framework was released in 2019 to help prevent and mitigate frailty. An interdisciplinary team of health system leaders, clinicians, and academics adapted the AVOID framework into an educational module for healthcare providers. This study evaluated the effectiveness of the module and provides recommendations for developers of eLearning modules.Materials and methodsThis study employed a convergent mixed-methods design. Participants included a diverse sample of healthcare providers from a Canadian health authority, including nurse educators, physiotherapists, and care aides, who completed the AVOID Frailty educational module through an online learning platform. Participants completed surveys before and after completing the module, probing their understanding of frailty management and perspectives on the module. A subsample of individuals who completed the module participated in one of four focus groups with the evaluation team. Quantitative survey data were analyzed descriptively, and qualitative focus group and survey data underwent an exploratory descriptive analysis led by two members of the evaluation team. Data were integrated during analysis where appropriate.ResultsThe module improved participants’ self-reported knowledge of frailty assessment, mitigation, and prevention. Participants valued the module’s length and content but identified a need for more interactive and visually engaging elements, as well as clearer guidance on practical implementation. Participants intended to use resources from the module, but noted that limitations of resources in the healthcare system could pose challenges for frailty prevention initiatives.ConclusionThis study suggests areas for improvement of the AVOID Frailty educational module, highlighting the importance of including healthcare staff perspectives when developing eLearning modules. Further, this work underscores the potential of targeted education to strengthen frailty care.